Kriteria Memilih Suami di Kalangan Mahasiswi Etnis Minangkabau - Hanivatul Khairat; Wilda Sari Nasution; Julfi Yanda; Syifa Wikri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
One of the uniqueness of Minangkabau ethnicity is the culture that is very close to Islam, as the Minangkabau philosophy of adat basandi syara syara basandi kitabullah. Phenomenology in choosing a partner is increasingly found among Minangkabau society, especially among students. Of course, the selection of a life partner cannot be separated from religion and customs, clearly the partner in question has certain criteria that make someone worthy of being a husband. In fact, this study aims to identify and analyze how the criteria for choosing a husband are among Minangkabau ethnic female students. This study uses a qualitative method with a phenomenological type. Data sources were taken through in-depth interviews with twenty-one informants selected using the purpuse sampling technique, consisting of female students at one of the state universities in Indonesia. All data were analyzed using the Miles and Huberman technique. The research findings found six criteria for choosing a husband among Minangkabau ethnic female students. The six criteria are i) Obedient to Allah, ii) Stable economy, iii) Coming from a good family, iv) Not physically disabled v) Not of the same tribe, vi) Not ajo piaman. The six criteria for choosing a husband in this finding can be used as a reference for all Minangkabau women in choosing a husband, because a husband with such criteria is based on religious teachings and customs. Salah satu keunikan etnis Minangkabau adalah kultur budaya yang sangat erat dengan agama islam, sebagaimana falsafah Minangkabau adat basandi syara syara basandi kitabullah. Fenomenologi dalam memilih pasangan semakin banyak ditemui dikalangan Masyarakat Minangkabau, terutama dikalangan mahasiswa. Tentu pemelihan pasangan hidup tidak terlepas dari agama dan adat istiadat, jelas pasangan yang dimaksud memiliki kriteria-kriteria tertentu yang menjadikan seseorang pantas untuk dijadikan suami. Justru itu penelitian ini bertujuan untuk mengidentifikasi serta menganalisis bagaimanakah kriteria memilih suami dikalangan mahasiswi etnis Minangkabau. Penelitian ini mengunakan metode kualitatif dengan jenis fenomenologi. Sumber data diambil melalui wawancara mendalam kepada dua puluh satu informan yang dipilih dengan Teknik porpuse sampling, terdiri dari mahasiswi di salah satu perguruan tinggi negeri di Indonesia. Seluruh data dianalisis dengan Teknik Miles and Huberman. Temuan penelitian mendapati enam kriteria memilih suami dikalangan mahasiswi etnis Minangkabau. Enam kriteria tersebut adalah i) Taat pada Allah, ii) Ekonomi stabil, iii) Berasal dari keluarga baik-baik, iv) Tidak cacat fisiknya v) Tidak sesuku, vi) Tidak ajo piaman. Enam kriteria memilih suami dalam temuan ini dapat dijadikan sebagai acuan untuk semua Perempuan Minangkabau dalam memilih suami, karena suami dengan kriteria demikian berdasarkan ajaran agama dan adat.